Targeting Epigenetic Regulation of miR-34a for Treatment of Pancreatic Cancer by Inhibition of Pancreatic Cancer Stem Cells - Nalls, Dara; Tang, Su-Ni; Rodova, Marianna; Srivastava, Rakesh K.; Shankar, Sharmila (PloS one, 2011)
MicroRNA-34a (miR-34a) is a transcriptional target of p53 and is down-regulated in pancreatic cancer. This study aimed to investigate the functional significance of miR-34a in pancreatic cancer progression through its epigenetic restoration with chromatin modulators, demethylating agent 5-Aza-2'-deoxycytidine (5-Aza-dC) and HDAC inhibitor Vorinostat (SAHA). Re-expression of miR-34a in human pancreatic cancer stem cells (CSCs) and in human pancreatic cancer cell lines upon treatment with 5-Aza-dC and SAHA strongly inhibited the cell proliferation, cell cycle progression, self-renewal, epithelial to mesenchymal transition (EMT) and invasion. In pancreatic CSCs, modulation of miR-34a induced apoptosis by activating caspase-3/7. Treatment of pancreatic CSCs with the chromatin-modulating agents resulted in the inhibition of Bcl-2, CDK6 and SIRT1, which are the putative targets of miR-34a. MiR-34a upregulation by these agents also induced acetylated p53, p21(WAF1), p27(KIP1) and PUMA in pancreatic CSCs. Inhibition of miR-34a by antagomiR abrogates the effects of 5-Aza-dC and SAHA, suggesting that 5-Aza-dC and SAHA regulate stem cell characteristics through miR-34a. In CSCs, SAHA inhibited Notch pathway, suggesting its suppression may contribute to inhibition of the self-renewal capacity and induction of apoptosis. Interestingly, treatment of pancreatic CSCs with SAHA resulted in the inhibition of EMT with the transcriptional up-regulation of E-Cadherin and down-regulation of N-Cadherin. Expression of EMT inducers (Zeb-1, Snail and Slug) was inhibited in CSCs upon treatment with SAHA. 5-Aza-dC and SAHA also retard in vitro migration and invasion of CSCs. The present study thus demonstrates the role of miR-34a as a critical regulator of pancreatic cancer progression by the regulating CSC characteristics. The restoration of its expression by 5-Aza-dC and SAHA in CSCs will not only provide mechanistic insight and therapeutic targets for pancreatic cancer but also promising reagents to boost patient response to existing chemotherapies or as a standalone cancer drug by eliminating the CSC characteristics.